AKR1C3 and Its Transcription Factor HOXB4 Are Promising Diagnostic Biomarkers for Acute Myocardial Infarction - Liang, Jingjing; Cao, Yue; He, Mingli; Li, Weiwen; Huang, Guolin; Ma, Tianyi; Li, Meijun; Huang, Yuli; Huang, Xiaohui; Hu, Yunzhao (Frontiers in Cardiovascular Medicine, 2021)
Background: A recent study disclosed that ferroptosis was an important myocyte death style in myocardial infarction (MI). However, the diagnostic value of ferroptosis regulators and correlated underlying mechanisms in acute myocardial infarction (AMI) remain unknown. Methods: Bioinformatical analyses were conducted to identify the candidate biomarkers for AMI, and the collected local samples were used to validate the findings via real-time quantitative PCR. Bioinformatical analysis and luciferase reporter assay were implemented to identify the transcriptional factor. Transient transfection and ferroptosis characteristic measurement, including glutathione peroxidase 4, malondialdehyde, iron, and glutathione, was performed to verify the ability of the candidate gene to regulate the ferroptosis of cardiomyocytes. A meta-analysis was conducted in multiple independent cohorts to clarify the diagnostic value. Results: A total of 121 ferroptosis regulators were extracted from previous studies, and aldo-keto reductase family 1 member C3 (AKR1C3) was significantly downregulated in the peripheral blood samples of AMI cases from the analysis of GSE48060 and GSE97320. HOXB4 served as a transcriptional activator for AKR1C3 and could suppress the ferroptosis of the H9C2 cells treated with erastin. Besides this, peripheral blood samples from 16 AMI patients and 16 patients without coronary atherosclerotic disease were collected, where AKR1C3 and HOXB4 both showed a high diagnostic ability. Furthermore, a nomogram including HOXB4 and AKR1C3 was established and successfully validated in six independent datasets. A clinical correlation analysis displayed that AKR1C3 and HOXB4 were correlated with smoking, CK, CK-MB, and N-terminal-pro-B-type natriuretic peptide. Conclusion: Taken together, this study demonstrates that AKR1C3 and HOXB4 are promising diagnostic biomarkers, providing novel insights into the ferroptosis mechanisms of AMI.